Southeast Asia's Transboundary Haze Pollution: Malaysian Youth Awareness Towards Indonesia's Commitment in The Post-Ratification of AATHP / Mohammad Zulhafiy ... [et al.] - Zulhafiy, Mohammad; Hino, Samuel Jose; Md Abas, Nur Farhana; Md Khalid, Nor Suhaiza (2021)
Transboundary pollution can be defined as a condition where the originated pollution that happens in one country disperses and spreads until it crosses the border of a country, whether through air or water as the pathways of the dispersed, which will cause damage to the environment of another neighbour country (OECD, 2013). In Southeast Asia, the annual series of transboundary haze pollution has become worse after the delay of the Indonesian government's ratification of the ASEAN Agreement on Transboundary Haze Pollution (AATHP). Indonesian lawmakers authorised the AATHP on September 16, 2014, making it the last ASEAN member state to adopt the agreement on January 20, 2015. Environmental issues such as transboundary haze pollution occur when a state adopts the UN's concept of environmental law which is the principle of state sovereignty whereby Hamid & Sein (2007, p.524-525) has described it as the ability of states to set and achieve economic goals that appear to be a substantial barrier to environmental conservation. The ASEAN practice of "quiet diplomacy" has also provided boundaries for the member states to have bilateral and multilateral cooperation to address this issue. Since some countries do not rely on state-owned legislation to hold Indonesia accountable, ASEAN faces difficulty in putting out fires once it has erupted (Tay, 1998). Indonesia's post-AATHP capacity to endure more robust regional initiatives was decreased (Hurley & Lee, 2020). This is because it even exempts Indonesia from accepting foreign firefighting assistance during transboundary haze problems (Greenpeace Southeast Asia, 2019). Indonesia has laws against illegal burning; however, they are ineffective due to poor enforcement and misaligned incentives (Hielmann, 2015). Since early 2019, the Indonesian Ministry of Environment and Forestry reported 68,400 acres of fires (Jong, 2019). It also clarified that the self-interests of both small Indonesian farmers and major plantation firms conflicting with steps to be taken to preserve the constitution (Hielmann, 2015). Almost every year, the haze has a destructive effect on Sumatra and Indonesia's part of Borneo, where smog from Indonesia blooms over the Southeast Asia region and spreads through the air into neighbouring Singapore and Malaysia (Amelia, 2017). In Malaysia, approximately 2,500 schools, including nearly 300 in the smog-hit capital of Kuala Lumpur, were forced to close due to rising health risks from uncontrollable blazing danger on the islands of Sumatra and Borneo (Al Jazeera, 2019). Meanwhile in Indonesia, at least two people, including a child, are dead from the deepening haze pollution in South Sumatra and five NGOs accused the Indonesian government of severe violations of human rights for their failure to monitor the Sumatra and Kalimantan fires (Soeriaatmadja, 2019).